Distinctiveness of symptoms of prolonged grief, depression, and post-traumatic stress in bereaved children and adolescents - Spuij, Mariken (Springer-Verlag, 2012)
Studies among adults have shown that symptoms of prolonged grief disorder (PGD) are distinct from those of bereavement-related depression and post-traumatic stress-disorder (PTSD). This study was an attempt to replicate this finding in two distinct samples of bereaved children (N = 197; aged 8–12 years) and adolescents (N = 135; 13–18 years), confronted with the death of a parent, sibling or other close relative. Using confirmatory factor analyses, we compared the fit of a one-factor model with the fit of a three-factor model in which symptoms formed three distinct, correlated factors. In both samples, findings showed that the model in which symptoms of PGD, depression, and PTSD loaded on separate factors was superior to a one-factor model and displayed excellent model fit. Summed scores on the PGD, depression, and PTSD items were significantly associated with functional impairment, attesting to the concurrent validity of the PGD, depression, and PTSD factors. The current findings complement prior evidence from adult samples that PGD is a distinct syndrome and suggest that PGD symptoms should be addressed in the assessment and treatment of bereaved children and adolescent seeking help following their loss.